Cash Waqf As Source Of Funding For Financial Technology Startups - Siti Nurjanah; Uswatun Hasanah (Jurnal Internasional Ekonomi Islam, 2021)
Productive management of cash waqf can be used as a new strategy to alleviate poverty and create prosperity for the community if it is managed properly and properly and can support economic stability. Cash waqf opens up unique opportunities to create investment to provide religious services, educational services and social services. Cash waqf is very potential but not popular, causing the role of cash waqf not yet optimal. Cash waqf in Indonesia has been legalized by national law and MUI. This is a positive opportunity to develop the economy, education and become a better instrument of community welfare, but there is still little understanding of the importance of cash waqf for development so that a stimulus is needed so that cash waqf management can be developed productively supported by financial technology, in the economic era 4.0 the majority of the use of digitizing economy, endowment money is used as capital for businesses, especially for companies with the ultimate goal of business empowerment community for are generally SMEs and companies startup through platform crowdfunding.